Health and safety regulations and stock returns: evidence from the 1974 Swedish legislative lottery. (6th August 2022) - Siming, Linus
Abstract : This article provides causal evidence on a long-standing controversy in the finance and labour literature, namely, whether better health and safety in the working environment is in the best interests of firm owners. While, on the one hand, an influential strand of the literature argues that improvements in workers' health and safety provision can increase costs and harm the market value of equity, another well-consolidated strand of the literature argues that such improvements can reduce costs and create shareholder value. It is empirically challenging to study the relation between the work environment and equity value due to their endogenous relation. To overcome this challenge, I utilize a historic natural experiment that uniquely isolates the effects of mandated investments in health and safety provision on firm market value: on 27 March 1974, the Swedish hung parliament drew a lottery ticket to decide on a legislative proposal that mandated companies to improve their employees' work environment. The lottery resulted in the approval of the proposal. I find that this outcome led to an immediate and sizable decrease in the market value of Swedish companies that persisted for several days.